Efficacy of The Essential Oil of Coriandrum sativum against Sitophylus oryzae (Coleoptera:Curculionidae) - Ayşe Yeşilayer; Kadriye Özlem Saygı (Turkish Journal of Agriculture: Food Science and Technology)
Recently, there has been a great interest in the use of natural products of plant origin due to the side effects of synthetic substances. Since synthetic chemicals used in the agricultural field a great threat to the environment and public health, many studies are carried out on the use of natural products from production to storage. Given the environmental and public health risks associated with synthetic chemicals commonly used in agriculture, extensive research efforts are focused on exploring the utilization of natural products throughout the entire agricultural process, from production to storage. The effiecy of Coriandrum sativum L. seed essential oil (Cs-EO) was evaluated in the laboratory condions against the rice weevil-Sitophylus oryzae L. adults. The Cs-EO essential oils were applied at four different dose rates (3%, 6%, 9% and 12%) on wheat and fumigant toxicity assay was recorded dead adults after 3, 5, 7, 9 and 11th days. In the 12%, the highest mortality 87.86 % and the lowest mortality at concentration of 3%, 23.28% and of the eleven days. In this study, GC-MS analysis of C. sativum was also determined at the same time. Cs essential oil was generated by steam distillation and compounds were identified by GC-MS analysis. GC-MS analysis of EOs from Cs seeds showed it to be reach linalool 79.12%. This study suggest that essential oil of Cs (Cs- EOs) can be used as alternatives to pesticides for management of stored pest control.